Arabic Validation of the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire, IUGA-Revised (PISQ-IR) - El-Azab, Ahmed S. (Int Urogynecol J, 2015)
INTRODUCTION AND HYPOTHESIS: To translate then assess the validity of the culturally adapted “the Pelvic Organ Prolapse and Incontinence Sexual Function Questionnaire - IUGA Revised (PISQ-IR)” to assess sexual health among Arabic-speaking women with pelvic floor disorders". METHODS: PISQ-IR was modified to consider cultural characteristics of Middle East. Final validity and reliability study included 172 women with urinary (UI), and/or pelvic organ prolapse (POP). Participants completed the questionnaire twice: at enrollment and 2 weeks later. RESULTS: Among sexually active women, good internal consistency was observed for 5 of the 6 scales in the adapted instrument: global quality (Cronbach’s coefficient α = 0.86), condition impact (α = 0.87), desire (α = 0.82), condition-specific (α = 0.74), and partner-related (α = 0.75). Internal consistency was acceptable for the Arousal Orgasm subscale (α = 0.66). However, among not sexually-active women, internal consistency was poor (α <0.6) for all four scales relevant to them (global quality, condition-impact, condition-specific, partner-related).. Lin’s concordance correlation coefficient measuring agreement between the test and retest measurements (CCC; a value of 1 represents perfect agreement) ranged from 0.81 to 0.87 for the not sexually active scales, except for condition impact (CCC=0.63.) For sexually active women, CCC was typically stronger, ranging from 0.85 to 0.96. CONCLUSIONS: PISQ-IR is an easy to administer, reliable, and valid questionnaire to assess sexual function in sexually active Arabic women with POP, UI or FI, but internal consistency was poor for Arabic women not sexually active.